The Impact of Chemotherapy and Body Mass Index on Cancer‐Related Fatigue in Colon Cancer Patients: A PROFILES‐Registry Study - Anneke Kastelein; Floortje Mols; Laura Kervezee; Niels H. Chavannes; Hans Gelderblom; Jacques Neefjes; Chris Hinnen (Cancer Medicine)
ABSTRACT Background Inflammation has been reported to drive cancer‐related fatigue (CRF). As both obesity and chemotherapy promote inflammatory responses, obese cancer patients may be at risk of more severe CRF, especially when receiving chemotherapy. Methods We analysed data of 333 colon cancer patients from four hospitals in the Netherlands (data derived from the PROCORE study). Fatigue was assessed with the general fatigue subscale of the Multidimensional Fatigue Inventory at four timepoints: at inclusion (T1), 4 weeks after surgery (T2), and 1 (T3) and 2 years (T4) after diagnosis. Linear mixed‐effects models were applied to evaluate the interaction between chemotherapy and body mass index (BMI) on the trajectory of fatigue. Results The two‐way interactions between time and chemotherapy (p = 0.047) and between time and BMI on fatigue (p = 0.041) were significant. Patients scheduled for chemotherapy reported more fatigue during the treatment phase, while patients not treated with chemotherapy showed a stable trajectory. Obese patients reported more fatigue at follow‐up compared to patients with a healthy BMI. The three‐way interaction between time, chemotherapy and BMI was not significant (p = 0.39). However, obese chemotherapy‐treated patients reported the highest fatigue 2 years after treatment (12.8, 95% CI: 10.6–14.9). Their mean fatigue score was higher compared to baseline (9.2, 95% CI: 7.3–11.0, p < 0.001) and obese patients not treated with chemotherapy (9.6, 95% CI: 7.0–12.2, p = 0.02). Moreover, this group reported more fatigue compared to healthy (8.1, 95% CI: 5.5–10.9, p < 0.001) and overweight (9.7, 95% CI: 7.2–12.3, p = 0.019) chemotherapy‐treated patients. Conclusion This study indicates that chemotherapy and BMI both influence long‐term fatigue in colon cancer patients. Proactive monitoring for CRF and lifestyle interventions may be needed for chemotherapy‐treated patients with a high BMI.